Transforming the prostatic tumor microenvironment with oncolytic virotherapy. (3rd July 2018) - Atherton, Matthew J.; Stephenson, Kyle B.; Tzelepis, Fanny; Bakhshinyan, David; Nikota, Jake K.; Son, Hwan Hee; Jirovec, Anna; Lefebvre, Charles; Dvorkin-Gheva, Anna; Ashkar, Ali A.; Wan, Yonghong; Stojdl, David F.; et al.
ABSTRACT: Prostate cancer (PCa) was estimated to have the second highest global incidence rate for male non-skin tumors and is the fifth most deadly in men thus mandating the need for novel treatment options. MG1-Maraba is a potent and versatile oncolytic virus capable of lethally infecting a variety of prostatic tumor cell lines alongside primary PCa biopsies and exerts direct oncolytic effects against large TRAMP-C2 tumors in vivo . An oncolytic immunotherapeutic strategy utilizing a priming vaccine and intravenously administered MG1-Maraba both expressing the human six-transmembrane antigen of the prostate (STEAP) protein generated specific CD8+ T-cell responses against multiple STEAP epitopes and resulted in functional breach of tolerance. Treatment of mice with bulky TRAMP-C2 tumors using oncolytic STEAP immunotherapy induced an overt delay in tumor progression, marked intratumoral lymphocytic infiltration with an active transcriptional profile and up-regulation of MHC class I. The preclinical data generated here offers clear rationale for clinically evaluating this approach for men with advanced PCa.